Subjectivity of Time Perception: A Visual Emotional Orchestration - Lambrechts, Anna; Mella, Nathalie M.; Pouthas, Viviane; Noulhiane, Marion (Frontiers in Integrative Neuroscience, 2011)
The aim of the present study was to examine how visual emotional content could orchestrate time perception. The experimental design allowed us to single out the share of emotion in the specific processing of content-bearing pictures, i.e. real-life scenes. Two groups of participants had to reproduce the duration (2, 4 or 6s) of content-deprived stimuli (grey squares) or differentially valenced content-bearing stimuli, which included neutral, pleasant and unpleasant pictures (IAPS). Results showed that the effect of content differed according to duration: for 2s, the reproduced duration was longer for content-bearing than content-deprived stimuli, but the difference between the two types of stimuli decreased as duration increased and was not significant for the longest duration (6s). For 4s, emotional (pleasant and unpleasant) stimuli were judged longer than neutral pictures. Furthermore, whatever the duration, the precision of the reproduction was greater for non-emotional than emotional stimuli (pleasant and unpleasant). These results suggest a dissociation within content effect on timing: relative overestimation of all content-bearing pictures limited to short durations (2s), and delayed overestimation of emotional relative to neutral pictures at 4s, as well as a lesser precision in the temporal judgment of emotional pictures whatever the duration. The angle of emotion processing in time perception allows us to discuss a few theoretical models proposed in the timing literature.